Hot corrosion behaviour of constant and pulsed current welded Hastelloy X in Na2SO4, V2O5, and NaCl salt mixture at 900 °C. (1st February 2022) - Sathishkumar, M; Manikandan, M; Arivazhagan, N; Arulmurugan, B; Kumaran Selvaraj, Senthil; Vignesh, M; Rajakumar, S; Rajkumar, S
Abstract: The high-temperature corrosion behavior of constant current gas tungsten arc (GTA) and pulsed current gas tungsten arc (PCGTA) welded Hastelloy X with different filler wires (C263 and ERNiCr-3) are studied for 50 cycles at 900 °C. Molten salt I (MS I) (75% Na2 SO4 + 25% V2 O5 ) and molten salt II (MS II) (75% Na2 SO4 + 20% V2 O5 + 5% NaCl) were coated on the welded specimens. MS II coated substrate shows the highest weight gain than MS I with a parabolic constant for GTA ERNiCr-3 as 21.440 × 10 –6 mg 2 /(cm 4 .s). Whereas PCGTA C263 welded sample with MS I, revealed parabolic constant (lowest) of 0.008 × 10 –6 mg 2 / (cm 4 .s). Based on the results, an increasing pattern of hot corrosion resistance of substrates is arranged as GTA ERNiCr-3 < GTA C263 < PCGTA C263 < PCGTA ERNiCr-3. PCGTA shows more refined grains, higher grain boundary volume, better corrosion resistance, and more protective phases like Cr2 O3, NiO, NiCr2 O4, CoCr2 O4, Al2 O3, NiFe2 O4, NbO than GTA weldment. But phases such as Fe2 O3, MoO3, and Cr2 S3 (non-protective phases) decrease corrosion resistance due to acid fluxing of alloying elements that promote the oxide scale exfoliation, spallation, chipping, and cracking. This study observed that PCGTA with C263 filler in MS I and MS II environment provides good corrosion resistance at high temperatures.